SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEREKRUTAN KASIR MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Welfriede Siregar; Masrizal Masrizal; Ibnu Rasyid Munthe (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
This study aims to solve the selection problem of recruiting employees to be placed in the cashier section at Growmart (Cab. Farming Business) - Bagan Batu Farm Shop. To facilitate the selection of cashiers at this company, it is done by building a decision support system that can help make it easier for companies to select prospective cashiers to be employed at the company. Decision support system built using the Simple Additive Weighting method. The criteria used in the DSS SAW method consist of psychological tests, interviews, health tests, education and work experience. The results of data processing from this research case study, obtained the 3 best cashier candidates with rank 1 is cashier 06 with a value of 1.00890, rank 2 is candidate for cashier 05 with a value of 1.00339, and rank 3 is candidate cashier 02 with a value of 0.99813.